Active disease requiring TNF-alpha-antagonist therapy can be well discriminated with different ASDAS sets: a prospective, follow-up of disease activity assessment in ankylosing spondylitis - (:unkn) unknown (CLINICAL & EXPER RHEUMATOLOGY, 2010)
Objective. To evaluate the validity of different ASDAS sets to assess disease activity in ankylosing spondylitis (AS) in comparison to standard activity assessment tools in routine clinical setting and to determine the best cut-off values for deciding active disease requiring TNF-alpha antagonist therapy. Methods. Two hundred consecutive AS patients (M/F:104/96) were enrolled. Mean (SD) age was 40.3 (11.7) and disease duration was 11 (8.5) years. Disease activity was assessed by four different ASDAS sets, BASDAI, patient and physicians' global assessments, ESR and CRP. The correlation between different parameters and ASDAS scores of patients requiring TNF-alpha antagonist therapy were determined. Results. At the time of the assessment 18.5% of the patients were only having NSAIDs, 43% were receiving sulphasalazine and/or methotrexate and 38.5% were under TNF-alpha antagonists. After the evaluation, 36 (18%) patients were decided to require TNF-alpha antagonist therapy, 33 (16.5%) patients were started sulphasalazine or methotrexate or their dose increased and 131 (65.5%) patients were decided to be stable without any requirement Pr a change in therapy. The patients requiring new-TNFa antagonist therapy had significantly higher ASDAS values. The ROC curve analysis revealed best-cut off values for ASDAS sets (ASDAS A: 3.28, ASDAS B: 3.07, ASDAS C: 2.38 and ASDAS D: 3.1) When standardised mean differences were compared, ASDAS B was the best set within the Others, but not significantly different from other ASDAS sets and standard assessment tools except acute-phase reactants. Conclusion. ASDAS sets perform well to discriminate TNF-alpha antagonist requirement in advanced AS patients. However BASDAI and patients or physician's global assessments also had acceptable performances in our clinical setting.
Keywords: Disease activity assessmen; ASDAS; ankylosing spondylitis